Analysis of the Temperament of Bushehr Historical Houses with Emphasis on the Effects of the Environment on the temperament of the space - Mohsen Afshary; Qasem Gedaali; Zahra Asadi (توسعه پایدار شهری)
In the architecture of historical houses, the environment, in addition to direct effects on how to choose effective climate solutions, has also influenced the temperament of living spaces. The current research aims to know the environment of Bushehr's historical houses and how it affects the temperament of the space.This research has been done with the aim of finding factors in the architecture of historical houses in Bushehr due to the effects of the environment on its mood through knowing the temperament characteristics of each space by studying the presence of the four characteristics of the environment as representatives of the four main moods on the spaces of the house. In researching the four characteristics of the environment, i.e. the four elements of water (earth moisture), wind (air flow), soil (building and connection with the earth) and fire (sun), each as a representative of the temperaments. main, have been considered. How the environment affects the temperament of the space and its effect on the architecture of the historical houses of Bushehr as the main question, and how each of the four indicators of the environment affects the temperament of the space as basic questions are considered. 16 houses in the historical context of Bushehr have been considered as a statistical population to analyze its temperamental characteristics in terms of how they are affected by the four elements.The samples were selected according to their distribution in the four historical neighborhoods of Bushehr, their different sizes, the number of different floors and the distance of each to the sea. The research is descriptive-analytical in terms of method and practical in terms of purpose and data collection is done in library and field study. The analysis was done in quantitative and qualitative method. Data analysis was considered to analyze the houses of the historical context of Bushehr in two ways: holistic (comprehensive) and detailed analysis in order to reach a general (inferential) result. The most important result of this research is the existence of diversity in the temperament of the house spaces in the historical context of Bushehr, so that each of the spaces has been formed according to the way of living and activities of the residents in it, and people with different temperaments can live based on their physical and mental needs.The architecture of the house in the traditional context of Bushehr has formed a whole in the interaction with the environment and people while being diverse.